Integrative analysis of the DNA methylome and transcriptome in uterine leiomyoma shows altered regulation of genes involved in metabolism, proliferation, extracellular matrix, and vesicles. Issue 5 (13th June 2022) - Carbajo‐García, María Cristina; Corachán, Ana; Juárez‐Barber, Elena; Monleón, Javier; Payá, Vicente; Trelis, Alexandra; Quiñonero, Alicia; Pellicer, Antonio; Ferrero, Hortensia
Abstract: Uterine leiomyomas (ULs) are the most common benign tumors in women of reproductive age. Despite the high prevalence, tumor pathology remains unclear, which hampers the development of safe and effective treatments. Epigenetic mechanisms appear to be involved in UL development, particularly via DNA methylation that regulates gene expression. We aimed to determine the relationship between DNA methylation and gene expression in UL compared with adjacent myometrium (MM) to identify molecular mechanisms involved in UL formation that are under epigenetic control. Our results showed a different DNA methylation profile between UL and MM, leading to hypermethylation of UL, and a different global transcriptome profile. Integration of DNA methylation and whole‐transcriptome RNA‐sequencing data identified 93 genes regulated by methylation, with 22 hypomethylated/upregulated and 71 hypermethylated/downregulated. Functional enrichment analysis showed dysregulated biological processes and molecular functions involved in metabolism and cell physiology, response to extracellular signals, invasion, and proliferation, as well as pathways related to uterine biology and cancer. Cellular components such as cell membranes, vesicles, extracellular matrix, and cell junctions were dysregulated in UL. In addition, we found hypomethylation/upregulation of oncogenes ( PRL, ATP8B4, CEMIP, ZPMS2‐AS1, RIMS2, TFAP2C ) and hypermethylation/downregulation of tumor suppressor genes ( EFEMP1, FBLN2, ARHGAP10, HTATIP2 ), which are related to proliferation, invasion, altered metabolism, deposition of extracellular matrix, and Wnt/β‐catenin pathway dysregulation. This confirms that key processes of UL development are under DNA methylation control. Finally, inhibition of DNA methyltransferases by 5‐aza‐2'‐deoxycitidine increased the expression of hypermethylated/downregulated genes in UL cells in vitro . In conclusion, gene regulation by DNA methylation is implicated in UL pathogenesis, and reversion of this methylation could offer a therapeutic option for UL. © 2022 The Pathological Society of Great Britain and Ireland.